The lost secret : unlocking the hidden chapters of Napoleon Hill's think and grow rich - Main, Monica (Waterside Productions, 2019)
"What if I told you that there are 2 lost chapters to the infamous Think and Grow Rich? And what if I told you that those 2 lost chapters reveal the MISSING SECRET to getting anything and everything you've ever wanted... and much, much more? There is a reason that this information was hidden from the mass public. It is because it was too powerful for the common man and woman to know. Times have changed. Not only are people ready to see this missing secret but they are much better equipped to use this power to change the trajectory of their lives, especially now more than ever in our chaotic, depressed, and anxiety-ridden society. For the first time ever, you'll finally come to know the REAL SECRET that Napoleon Hill always wanted us to know but couldn't get it published in his time. This is his gift, his legacy, and his secret from beyond the grave."--